Navigating the Drivers, Challenges, and Required Institutional Reforms for Indonesia’s Accession to the CPTPP - Pinonto'an, Nabila Dinda Shalsabilla (Kementerian Luar Negeri Republik Indonesia, 2025)
This article examines Indonesia’s policy direction in pursuing accession to the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP). By reviewing relevant literature, policy documents, and official statements, the study addresses two main questions: (1) What strategic, economic, and political motivations drive Indonesia’s decision to seek accession to the CPTPP? and (2) What institutional reforms are necessary to align with the multidimensional commitments of the CPTPP? The analysis finds that Indonesia's motivations are driven by the need to increase exports, attract investment, strengthen competitiveness, and deepen integration into global supply chains. However, Indonesia faces challenges in labor, government procurement, state-owned enterprises, and environmental standards. Using a qualitative case study, this study finds that while Indonesia shows partial regulatory alignment with CPTPP commitments, key gaps persist due to protectionist policies and institutional limitations. While the Indonesian government demonstrates political interest and intent, a gap remains between international commitments and domestic preparedness. The article concludes that Indonesia’s CPTPP accession plan requires significant regulatory adjustments and cross-sectoral coordination. The findings provide theoretical insight on institutional adaptation and practical guidance for regulatory reform to align Indonesia with CPTPP standards.